Sustainable application of rice-waste for fuels and valuable chemicals-a mini review - Zhang, Wenwen; Xu, Xiaoyu; Yuan, Yongjun; Wang, Zichun (Frontiers in Chemistry, 2023)
The global annual production of rice is over 750 million tons, and generates a huge amount of biomass waste, such as straw, husk, and bran, making rice waste an ideal feedstock for biomass conversion industries. This review focuses on the current progress in the transformation of rice waste into valuable products, including biochar, (liquid and gaseous) biofuels, valuable chemicals (sugars, furan derivatives, organic acids, and aromatic hydrocarbons), and carbon/silicon-based catalysts and catalyst supports. The challenges and future prospectives are highlighted to guide future studies in rice waste valorization for sustainable production of fuels and chemicals.